The other story [videorecording (DVD)] - Nesher, Avi; Blum, Maʻayan; Dagan, Mayah, 1977-; Gabay, Sasson (Strand Releasing, 2019)
A suspenseful, poignant, and humorous story through the eyes of two rebellious young women from two troubled families that tangle in the most unexpected ways in Jerusalem.